58.6k views
3 votes
I need help on this I will give five stars

I need help on this I will give five stars-example-1
User Vin
by
5.1k points

1 Answer

3 votes

Answer:

Option (3)

Option (3)

Option (2)

Explanation:

(3x² + 2x - 2)×(x² - 2) = x²(3x² + 2x - 2) - 2(3x² + 2x - 2) [By distributive law]

=
(3x^(4)+2x^(3)-2x^2)-(6x^(2)+4x-4)

=
3x^4+2x^3-2x^2-6x^2-4x+4

=
3x^4+ 2x^3-8x^2-4x+4

Therefore, Option (3) will be the answer.


-(75x^3y^2)/(-5x^2y)=(75)/(5)* (x^3)/(x^2)* (y^2)/(y)

= 15xy

Therefore, Option (3) is the answer.

-3x²y) 12x³y² + 9x²y³(-4xy - 3y²

12x³y²

0 + 9x²y³

+ 9x²y³

0

Therefore, (-4xy - 3y²) will be the quotient.

Option (2) will be the answer.

User Angoru
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.